Implementasi Website K-Etik untuk Digitalisasi Manajemen Etik Penelitian di Universitas YARSI - Putra, Rio Griya; Herlyansyah, Hafidz Putra; Windriyani, Paramaresthi; RS, Qomariah (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
The K-Etik Website was developed by Universitas YARSI as a solution to inefficiencies in research ethics management, which had previously been conducted manually, often leading to delays, inefficiencies, and a lack of transparency. This study aims to create a digital application capable of accelerating the review process and enhancing transparency in the management of ethics documents. The Scrum methodology was applied to facilitate collaboration between developers and users, integrating modern technologies such as React.js for the user interface, Node.js for the server, and MongoDB for database management. The application evaluation was conducted through black-box testing, indicating that the application meets the specified requirements, including user authentication, document submission workflows, and real-time progress tracking. System Usability Scale (SUS) testing yielded an average score of 81.1, classified as “Excellent,” signifying the application's high usability and readiness to support ethics management in research. Through digitalization via the K-Etik application, research ethics management at Universitas YARSI has become more efficient and transparent, strengthening accountability and responsiveness in the ethics document review process. The study concludes that this application provides a comprehensive digital platform to support a structured and accountable research environment at Universitas YARSI.